The Implementation of Morals Education at Madrasah Ibtidaiyah Negeri 2 Bengkulu City - Mindani Mindani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
This research aims to determine how the implementation of moral education in Madrasah Ibtidaiyah Negeri 2 (MIN 2) Bengkulu City and the factors that support and hinder it. Implementation of informants in this study were the head and vice principal of the school, teachers, students, and parents while the instruments used were interviews, observation, and documentation. The data obtained were then analyzed descriptively qualitatively and it was found that MIN 2 is a school that prioritizes moral education where the success of education is seen from how far students implement morals in their lives. Some of the steps taken by this school are conducting Tahfizul Quran education, guidance in wudhu, prayer and dzikir as well as adab guidance: in science assemblies, during recess, to the canteen, eating and drinking, in the school environment, returning home, and at home. The factors that support this success are a strong commitment from the school, teachers and foundations as well as the existence of clear technical instructions for the implementation of guidance. However, there is an inhibiting factor, namely sometimes there is still a lack of cooperation between parents and the school